Addressing car dependency in Cape Town: Reviewing how the Citys mobility and spatial frameworks can transcend car-oriented urbanism - Mpanang'ombe, Wrixon (School of Architecture, Planning and Geomatics, 2023)
This dissertation presents research conducted by Wrixon Mpanang'ombe titled ‘Addressing car dependency in Cape Town: Reviewing how the city's mobility and spatial frameworks can transcend car-oriented urbanism'. The research stems from a background of the need to address problems associated with the dominance of cars in cities. The problems include carbon emissions contributing to climate change, road safety issues, pollution and other public health challenges, but also inequitable accessibility favouring private car users, among many other problems. Also, the research is motivated by and in response to the argument by Newman and Kenworthy (2015) that cities are experiencing an end to car dependency. However, since this argument is made based on Global North contexts, researching what an end to car dependency might imply for Southern cities is very relevant. Therefore, this research situates in Cape Town to explore how the City of Cape Town is currently dealing with the issue of transitioning away from car dependency and caroriented urbanism. The research explores this by deploying an analysis of the discourse around issues addressing car dependency and car-oriented urbanism in the City's key transport and spatial planning frameworks. The frameworks were analysed through a series of assessment criteria that were derived from the literature review. Three main gaps emerged through the research: (1) the reluctance to call out car dependency as a major transport problem in the city, (2) the focus on costs for low-income groups in the City's transport planning objectives while overlooking the car dependency in medium- and high-income groups, and (3) the inadequate spatial alignment of plans with the varying urban fabrics (i.e., based on Newman's and Kenworthy's (2015) theory of urban fabrics) and therefore not positioned to leverage the potential of rejuvenating urban fabrics as a pathway toward ending car dependency. The research further suggests that to address these gaps, the key frameworks should be repositioned to explicitly name car dependency as a major problem for the urban mobility system, but also the various urban fabrics should be mapped and aligned with the City's transport and spatial plans and land use policies.